"Benign" metastasizing meningiomas. - Som, P M; Sacher, M; Strenger, S W; Biller, H F; Malis, L I (American Journal of Neuroradiology, 1987)
Less than one in 1000 meningiomas metastasizes. Although the angioblastic and hemangiopericytic tumors are believed by some authors to metastasize with a greater frequency than the other histologic forms of meningioma, most investigators believe that neither the histologic pattern, local aggressiveness, size, nor location of the tumor can be used accurately to predict which tumors will metastasize. Three new cases are presented, bringing the total reported number of metastasizing meningiomas to 113. If the angioblastic meningiomas and hemangiopericytomas are eliminated from this group, 69 reported cases of "benign" metastasizing meningioma remain.